Um fantasma da mente? - Alves Fernandes, Darley (Con-Textos Kantianos. International Journal of Philosophy, 2021)
Taking Kant’s suspicion of the morality (moral law) as a simple phantom of the mind as a departing point, we are intending to investigate the central role of the moral consciousness, taken here both as the possible source of this illusion so much as the premise through which one can infer the normativity of reason and assure the reality of duty and of our moral experience. Despite the fact this suspicion be somehow inevitable and remains in the philosopher’s mind as a kind of threat, it has been contrasted with a factual perspective of morality – according to which the experience of morality as an unconditional obligation is by itself an evidence of its intrinsic origin in reason.
Keywords: Illusion; moral consciousness; duty; respect; validity